ЕКСПЕРИМЕНТАЛЬНО-МОДЕЛЬНІ ДОСЛІДЖЕННЯ ВПЛИВУ РОЗОСЕРЕДЖЕНОЇ ГЕНЕРАЦІЇ НА ВИНИКНЕННЯ АСИНХРОННИХ РЕЖИМІВ В ОБ’ЄДНАНІЙ ЕНЕРГОСИСТЕМІ УКРАЇНИ - Буткевич, О.Ф.; Гурєєва, Т.М.; Юнєєва, Н.Т.; Слободян, А.Р. (Інститут електродинаміки НАН України, Київ, 2024)
The results of experimental and modeling studies of the distributed generation sources (DG) influence on the occurrence in the Interconnected Power System (IPS) of Ukraine asynchronous modes (AM) caused by accidents in its main electrical network are presented. According to simulation scenarios it was assumed that the DG power was introduced into electrical distribution networks instead of the power units of thermal power plants of the IPS of Ukraine which were destroyed as a result of missile attacks by the Russians. In the absence of information about DGs, certain generalizations and assumptions are made regarding the possibility of DG groups modeling of in the form of turbine generators with different inertia constants. Various scenarios of the accidents occurrence and the functioning of relay protection and anti-emergency automation devices were considered. Conducted studies results show that the DG introduction into distribution electrical networks does not contribute to the AM occurrence in the main electrical network of the IPS of Ukraine. References 11, figures 10, tables 3.